Monitoring, Evaluation and Learning for Adaptation - Njuguna, Lucy Wanjiku; Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
As climate change impacts intensify, strengthening the capacity of stakeholders to monitor and evaluate adaptation is critical for informed planning and decision-making. Tracking adaptation helps generate evidence on what works, for whom, where, how, and under what conditions. This presentation highlights key foundations for robust adaptation assessment, including the use of context-specific indicators and practical tools. It was delivered through the AGNES Climate Leadership Program to support evidence-based adaptation planning and reporting.